You should get for, the answer of,Originally Posted by becky
Please double check my work - just doesn't 'feel' right and I've always had a problem with what I call 'three stacked fractions'.
Instructions: Compute the derivative of the given function .
h(u) = 1/square root of u
My solution: h'(u) lim h->0 1/square root x+h - 1/square root u/h=
square root u/x+h - square root x+h/u /h(square root x+h)(square root u)=
square root u(x+h) - square root x+h(x+h/h(square root u)(x+h)^2=
-square root x.